2021
DOI: 10.3390/nu13051442
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Non-Alcoholic Fatty Liver Disease (NAFLD) and the Role of Sugary Food Consumption and Other Dietary Components in Its Development

Abstract: NAFLD is the world’s most common chronic liver disease, and its increasing prevalence parallels the global rise in diabetes and obesity. It is characterised by fat accumulation in the liver evolving to non-alcoholic steatohepatitis (NASH), an inflammatory subtype that can lead to liver fibrosis and cirrhosis. Currently, there is no effective pharmacotherapeutic treatment for NAFLD. Treatment is therefore based on lifestyle modifications including changes to diet and exercise, although it is unclear what the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(82 citation statements)
references
References 166 publications
0
50
1
1
Order By: Relevance
“…Finally, excess dietary fat and carbohydrate intake also take part in the NAFLD pathophysiology [54,55]. Many studies confirmed that a long-term high-fat diet promotes the development of NAFLD [56][57][58].…”
Section: Ffa Accumulationmentioning
confidence: 99%
“…Finally, excess dietary fat and carbohydrate intake also take part in the NAFLD pathophysiology [54,55]. Many studies confirmed that a long-term high-fat diet promotes the development of NAFLD [56][57][58].…”
Section: Ffa Accumulationmentioning
confidence: 99%
“…Available studies have demonstrated that calorie-restricted diet, dietary composition, and the frequency of food intake could have an impact on the intrahepatic triglyceride content. 12 13 In addition, low glycemic food enriched with fruits and vegetables based on a calorie-restricted diet would improve MAFLD-related parameters. [14] Among these, a Mediterranean dietary pattern with restricted cholesterol/saturated fatty acid was recommended for MAFLD patients by major guidelines.…”
Section: Weight Loss: Fundamental Treatment Of Mafldmentioning
confidence: 99%
“…For instance, weight reduction of up to 5–10% caused 58%-90% of NASH and 45% of fibrosis resolution [ 42 , 43 ]. Dietary habits are one of the common etiological factors associated with the development and severity of NAFLD [ 44 ]. A recent meta-analysis reported that individuals who consume a high amount of red meat and soft drinks might be more likely to develop NAFLD.…”
Section: Introductionmentioning
confidence: 99%